2022
DOI: 10.1007/s00018-022-04155-y
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin reductase 3 suppression promotes colitis and carcinogenesis via activating pyroptosis and necrosis

Abstract: BackgroundTxnrd3 as selenoprotein play key roles in antioxidant process and sperm maturation. In ammatory bowel diseases, such as ulcerative colitis and Crohn's disease are becoming signi cantly increasing disease worldwide in recent years which are proved relative to diet especially selenium intake. MethodsIn the present study, 8-week-old C57BL/6N male Txnrd3-/-, Txnrd3-/+, Txnrd3+/+ mice weight 25-30g were randomly chosen and each group 30 mice. Feed 3.5% DSS drinking water and normal water continuously for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Furthermore, the activated inflammasome complex triggers caspases, thereby contributing GSDMD cleavage and macrophage pyroptosis (Evavold et al, 2018;Russo et al, 2021). Pyroptosis is an inflammatory cell death process and has become a novel target for UC treatment (Corcoran, Halai, & Cooper, 2021;Liu et al, 2022). Recent studies have confirmed that it is effective to alleviate colonic inflammation via suppressing caspase-1/GSDMD-mediated macrophage pyroptosis (Wang et al, 2022;Zhang et al, 2022).…”
mentioning
confidence: 99%
“…Furthermore, the activated inflammasome complex triggers caspases, thereby contributing GSDMD cleavage and macrophage pyroptosis (Evavold et al, 2018;Russo et al, 2021). Pyroptosis is an inflammatory cell death process and has become a novel target for UC treatment (Corcoran, Halai, & Cooper, 2021;Liu et al, 2022). Recent studies have confirmed that it is effective to alleviate colonic inflammation via suppressing caspase-1/GSDMD-mediated macrophage pyroptosis (Wang et al, 2022;Zhang et al, 2022).…”
mentioning
confidence: 99%
“…Gpx family has prominent antioxidant effects, and its reduced activity resulted in a weakened ROS-scavenging capacity of cells, thus affecting the entire growth phase of cells ( 56 ). Txnrd family exerted an irreplaceable antioxidant role, in addition, bound to many proteins and involved in regulating cell growth such as inhibiting apoptosis and autophagy ( 57 , 58 ). Sels, a widely expressed transmembrane protein located in the ER, is critical for ER stress by eliminating misfolding proteins and regulating oxidative stress, apoptosis, and autophagy ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of TXNRD3 in cancer development is less known than the role of TXNRD2. It has been shown that knockout of TXNRD3 in mice resulted in increased severe ulcerative colitis and lesions than in corresponding wild-type mice, conditions that are known to be a risk factor for the development of colorectal cancer [ 114 ]. Furthermore, overexpression of TXNRD3 in a murine colon cancer cell line (CT26) increased oxidative stress and necrosis in these cells [ 114 ].…”
Section: Impact Of Selenoproteins On Cancermentioning
confidence: 99%
“…It has been shown that knockout of TXNRD3 in mice resulted in increased severe ulcerative colitis and lesions than in corresponding wild-type mice, conditions that are known to be a risk factor for the development of colorectal cancer [ 114 ]. Furthermore, overexpression of TXNRD3 in a murine colon cancer cell line (CT26) increased oxidative stress and necrosis in these cells [ 114 ]. Despite limited evidence, these findings intimate that TXNRD2 and TXNRD3 also inhibit oxidative stress via the thioredoxin system in cancers as TXNRD1, thereby promoting cancer cell resistance to cell death.…”
Section: Impact Of Selenoproteins On Cancermentioning
confidence: 99%